Assédio moral no trabalho: relações com bases de poder do supervisor, autoconceito profissional e satisfação no trabalho - Ferraz, Ana Maria Souto (2009)
The concern with the effects of the new organization has presented as a consequence greater emphasis to the study of variables related to man as a worker and the organization itself to the impact that may arise among employees and organizational outcomes. Harassment at work is emerging as an important theme in this context and as a new construct, justified the need for further studies, to define the phenomenon within organizational, and enrich your understanding with other constructs of the area. The exploration of moral harassment by the frequency of occurrence perceived of hostile acts and the emotional impact felt by victims of harassment is a new subject and is part of the proposed research. The aim of this study was to investigate the influence of types of power bases (expertise, coercion, reward and legitimate) in the moral harassment (perceived and felt) at work, and in the workers professional self-concept (factors: achievement, confidence, competence and health) and in the job satisfaction (factors: the organizational support, the usefulness of social organization and work with the affective relationship at work, with professional recognition). This is a field study and ex-post facto, crosssectional, exploratory and correlational study. The variables were assessed by valid and reliable scales, all self-administered. The study included 191 volunteers, mean age 28 years (SD = 8), and 64.6% female, from different organizations. Data analysis was done by descriptive statistics and regression analysis, having been used the statistical package SPSS. Education level ranged from primary school through graduate track, which 74.6% of participants had high school and worked in mostly administrative duties (29.5%) and attendance/reception (13.1%), with 91% employees of private organizations. The results showed that power bases did not predict the perception nor the emotional impact of moral harassment, and these, in turn, even mediate the relationship between power bases and professional self-concept and job satisfaction. Test redesigned model that brought power bases and moral harassment as antecedents of self-concept and job satisfaction was conducted by means of multiple linear regressions standard. The results showed that power base of expertise explained a small proportion of the variance of professional self-concept of competence. But the main predictor of professional self-concept and satisfaction with social utility of the organization and the work was the perception of harassment training at work. It can be concluded that perceived harassment at work seems to generate among the workers more negative effect than feeling humiliated by hostile acts or by perception of use by the supervisor power bases identified in the literature as impacting consequent negative variables investigated in this study.